(untitled) (Research, Society and Development, 2021)
The Post-Graduation in Medicine is a peculiar step in Medical Education, having in the Medical Residency its form of specialization of a regular and permanent character, and considered the gold standard in the training of doctors. The state of Maranhão has one of the lowest averages, with respect to the ratio of medical professionals for each group of one thousand people. In 2016, the residency in Pediatrics was implemented in the state health network and we seek through this work to understand the perception of doctors, residents in Pediatrics and preceptors, about their experience in this Medical Residency Program. This is a descriptive and analytical study, with a qualitative approach, and we used the semi-structured interview as a method for data collection where we interviewed 7 residents and 13 preceptors. The research was carried out from May 2019 to March 2020, in a state referral hospital in Pediatrics. The results reaffirm the importance of medical residency, as well as pointing to the need to redimension the policy of medical preceptorship of the State Health Secretariat, with regard mainly to the importance of clinical protocols in network hospitals, continuing education in the training of doctors preceptors, review of contracts with medical groups that include responsibility for medical preceptorship, implementation of a preceptor assessment process and definition of their pedagogical skills and technical responsibilities.